Solar Power Renaissance - Srinivasan, Taejas P. Srinivasan; Rajamani, Divakar (International Journal of Supply Chain Management, 2016)
The U.S. is witnessing an unprecedented growth in renewables, particularly wind and solar energy, thanks to a number of enablers including government subsidies, government mandates to utilities, impressive technological growth, price collapse in silicon production costs, and the geo-political uncertainty around fossil fuel production. While wind energy has more favorable market conditions due to its more relatively mature state and inherent advantages such as all-day production, the solar energy production is becoming more competitive primarily due to the rapidly declining supply chain costs and scale economy in solar panel production. In this paper, our focus is on the underlying factors for the supply chain cost decrease, which has led to a more attractive profitability potential in the industry, despite the price pressure on the revenue. However, we find no evidence that the supply chain cost gains can continue to dramatically lower the cost of production much further. This means that manufacturers need to find new ways to improve the manufacturing efficiencies subject to the theoretical limits on energy conversion efficiencies or move up the technology maturity curve to the next generation solar technology. If they stay too long close to such theoretical conversion efficiency this will be an evening twilight, and yet if they can switch at the right time to ride the technology curve, it will be a morning twilight. We begin with the overall market growth drivers for solar panels in Section 1 and their impact on the solar panels manufacturers. In section 2, we devote our attention to the efficiency drivers for various solar technologies. These include both the conventional ones in place today as well as disruptive technologies on the horizon and potential drivers that would make them more affordable. We conclude this paper in Section 3 with areas to explore as next steps.